Effect of secondary cold-rolled and annealing on ridging and corrosion properties of 430 ferritic stainless steel - RuiKun Wang; ZeXuan Li; XueZeng Yang; LeFeng Cheng (Journal of Materials Research and Technology)
Effects of the secondary cold rolling and annealing process on the surface ridging and corrosion resistance of 430 ferritic stainless steel were investigated by surface analysis and electrochemical tests. Results demonstrate that secondary cold rolling (80 % deformation) with annealing at 860 °C significantly refines grains and increases γ-fiber weaving. Microstructure optimization increases the grain boundary density and then promotes Cr diffusion, forming a dense Cr2O3-rich passivation film. This lowers self-corrosion current density by 58 %. Additionally, refined and homogenously distributed M23C6 precipitates further reduce Cr depletion zones. Electrochemical tests revealed that the optimized process specimens enhanced charge transfer resistance by 228 %, confirming superior passivation film stability. This work shows that secondary cold rolling and annealing synergistically suppress ridging through strain homogenization while enhancing corrosion resistance via grain boundary engineering and Cr2O3 film optimization.